Effects of three conventional drying methods on the lipid oxidation, fatty acids composition, and antioxidant activities of walnut (Juglans regia L.). Issue 7 (18th May 2016) - Qu, Qingli; Yang, Xiaoying; Fu, Maorun; Chen, Qingmin; Zhang, Xiaohui; He, Zhiping; Qiao, Xingguo
ABSTRACT: Three walnut ( Juglans regia L.) drying methods (sun drying, direct oven drying, and intermittent oven drying) were employed, and the consequent changes in lipid oxidation attributes, such as acid value (AV), peroxide value (POV), saponification value (SV), fatty acid composition, and antioxidant activity [including reducing power, superoxide anion scavenging activity, 1, 1-diphenyl-2-picrylhydrazyl free radical scavenging activity (DPPH), lipoxygenase (LOX) activity, total phenols content (TPC), and total flavonoids content (TFC)] were investigated in this study. Sun drying resulted in the highest AV, POV, and SV, followed by direct oven drying and intermittent oven drying. Antioxidant activities and related compounds, TPC and TFC, were initially increased and then declined during drying, and a significant correlation was found between antioxidant activity and TPC and TFC. The LOX activities of all samples showed an increasing trend, although those of the sun-dried samples were the lowest. The walnuts dried with the intermittent oven drying method contained more linoleic acid than those dried by direct oven drying. Overall, intermittent oven drying appears to be a promising strategy for fresh walnut drying.